Dislocation-mediated reversible grain rotation - Chengpeng Yang; Zhanxin Wang; Zihao Zhang; Yufeng Zhao; Jiao Teng; Qixun Guo; Yan Ma; Lixing Kang; Lihua Wang; Xiaodong Han (Materials Research Letters)
Atomic-scale grain rotation processes in NC AuCu alloy are captured in situ. We discovered a full dislocation-mediated reversible grain rotation that has rarely been reported before. The results show that, with loading, full dislocations nucleate, glide across the grain to the grain boundary (GB) and then accumulate at the GB, resulting in grain rotation. With unloading, full dislocations escape from GB and annihilate at the opposite GB or free surface, which leads to the reversible grain rotation. The current study provides direct evidence that both intragranular dislocation and GB plasticity can occur simultaneously during deformation, and comprehensive our understanding of the NC alloy deformation mechanism.